Endoscope-Assisted Microsurgery in Pediatric Cases With Pineal Region Tumors: A Study of 18 Cases Series - Cai, Yuankun; Xiong, Zhongwei; Xin, Can; Chen, Jincao; Liu, Kui (Frontiers in Surgery, 2021)
Background An endoscope-assisted technique was recently introduced to microsurgery (MS) and may compensate for the disadvantages of MS for deep-seated lesions. This study was performed to identify the effectiveness and safety of endoscopic-assisted microsurgery (EAM) and share our experience of EAM for pediatric cases with pineal region tumors. Method We retrospectively analyzed the clinical data of consecutive pediatric cases with pineal region tumors treated by EAM or MS from January 2016 to June 2020. These data included the patient population, clinical manifestations, preoperative examination findings, surgical approach, pathological results, and clinical outcomes. The clinical outcomes were analyzed in the EAM group and MS group with a focus on the gross total resection (GTR) rate, postoperative hydrocephalus remission rate, and Karnofsky performance score (KPS). Studies on the surgical management of children with pineal region tumors in the last decade were reviewed. Result Eighteen children successfully underwent tumor resection via MS (n = 8) or EAM (n = 10). The children’s mean age was 11.4 ± 4.7 years, and the male to female ratio was 7:2. Seventeen patients (94.4%) complicated preoperative hydrocephalus, and 16 (88.9%) presented headache with nausea and/or vomiting. The pathological examination revealed germ cell tumors in 11 (61.1%) patients, neuroepithelial tumors in 4 (22.2%) patients, and a pineoblastoma, arachnoid cyst, and atypical teratoid rhabdoid tumor in 1 (5.6%) patient each. GTR was more commonly achieved in the EAM than MS group (80.0% vs. 50.0%, respectively), and the postoperative hydrocephalus remission rate was higher in the EAM than MS group (87.5% vs. 50.0%, respectively). At a mean follow-up time of 23.6 ± 11.5 weeks, the mean improvement of the KPS 6 months postoperatively was greater in the EAM than MS group (24.0 ± 9.7 vs. 17.5 ± 7.1 points, respectively). Conclusion EAM combines endoscopic and microsurgical techniques and can be safely and effectively performed to achieve GTR of pineal region tumors in pediatric patients. In children with pineal region tumors who have obstructive hydrocephalus, EAM provides a new way to relieve hydrocephalus in one-stage surgery by opening the cerebral aqueduct.